Identification Of Shear Strain On The Surface Ground Of Wangi-Wangi Island, Southeast Sulawesi, Indonesia, Using Nakamura’s Technique and The Possibility Of Its Impacts - Manan, Abdul; Puspitafuri, Cindy; Chahyani, Rani; Irawati; Pertiwi, Imanuela Indah (UIR PRESS, 2023)
This research was conducted to determine the possible impact of an earthquake on the mainland of Wangi-Wangi Island based on the presence of shear strain on the surface ground (γ). The size of γ is obtained by multiplying the ground susceptibility index and the acceleration of basement ground or PGA using Nakamura’s technique. The data used are microtremor data and earthquake data from 1920 to 2020 sourced from the USGS. Microtremor data are obtained from the results of filtering ground vibration signals using a Band Pass Filter in the frequency range between 0.5 to 25 Hz. Ground vibration signals were recorded at 47 measurement points spread over the surface of Wangi-Wangi Island within 29.25 to 48.16 minutes. Furthermore, the microtremor data were processed using the HVSR (Horizontal to Vertical Spectral Ratio) method. The use of earthquake data must meet the requirements for a surface magnitude (MS) ≥ 5.0 SR and an earthquake epicenter depth (h) ≤ 45 km. The results obtained are the γ sizes of Wangi-Wangi Island in the order of 10-06 to 10-03. Based on the size distribution, it is known that the majority of the Wangi-Wangi Island area has the potential to experience cracks and land subsidence due to settlements if an earthquake occurs, and only a portion of the area is vibrating. In addition, it is also known that the mainland of Wangi-Wangi Island is not prone to landslides and liquefaction because γ<10-2.